AB1006 Power-doppler technique in paget's disease of bone: a new monitoring tool of therapeutic response. study on 43 patients. (15th June 2017) - Artusi, C; Mastaglio, C; Arnoldi, C; Galbiati, V; Meroni, PL
Abstract : Background: To date the evaluation of the disease activity and the monitoring of the therapeutic response of patients affected by Paget's disease of bone is based only on clinical and hematological data. However, in clinical practice the management of these patients is still challenging. Previous angiographic and histological studies have revealed that the accelerated bone turnover is associated with an increased blood flow and hypervascularity, suggesting a role of high-resolution sonography with power-Doppler (PD) and color- Doppler (CD) in Paget's disease. Our preliminary data demonstrated that this technique shows not only the alterations of the pagetic bone profile, but also the hypervascularization of the osteoperiosteal-layer, both at the diagnosis and during follow-up. Objectives: To validate the PD technique as a useful tool not only for the diagnosis of Paget's disease of bone but also for the evaluation of the disease activity and for the monitoring of the therapeutic response. Methods: Forty-three consecutive patients affected by Paget's disease of bone and treated with neridronate were followed up over the last ten years. Patients were classified in eight clinical patterns defined by the presence of bone alkaline phosphatase elevation over the normal range (BAP+), bone pagetic pain as visual analogue scale ≥30 (VAS+) and PD alterations of osteoperiosteal vascularization (PD+). Data were analyzed by Fisher exact test (two tails) to assess the associations between BAP+, VAS+ and PD+ at different times during follow up: before the start of the therapy, after the first, the second and the third neridronate cycle of therapy, and at the end of all cycles. Results: At any time BAP+ and VAS+ were not associated. A trend of association between VAS+ and PD+ could be observed only after the first neridronate cycle. In contrast, the association between BAP+ and PD+ was statistically significant before the therapy, at the end of all cycles of therapy and after the second one, but not after the first one. Conclusions: The lack of association between VAS+ and PD+ or BAP+ may be due to the difficulty of the patients in identifying and quantifying the pagetic pain, and suggests the weakness of the clinical criteria in defining the disease activity. Otherwise, PD technique proves to be a fast, reliable and not expensive tool, which is also very useful for monitoring/achieving better control of Paget's disease of bone. References: Adami S., et al. Italian guidelines for the diagnosis and treatment of Paget's disease of bone. Reumatismo, 2007; 59(2):153–168. Singer F.R., et al. Paget's Disease of Bone: An Endocrine Society Clinical Practice Guideline. J Clin Endocrinol Metab, 2014; 99(12):4408–4422. Mastaglio C., et al. Characterization of Osteocortical-Periosteal Layers by High-Resolution Sonography Using a Doppler Technique in Paget's Disease of Bone. JDMS, 2008; 24(3):136–144. Disclosure of Interest: None declared